Anti-Müllerian hormone as an ovarian reserve marker in women with the most frequent muscular dystrophies. Issue 23 (5th June 2020) - Parmova, Olesja; Vlckova, Eva; Hulova, Monika; Mensova, Livie; Crha, Igor; Stradalova, Petra; Kralickova, Eva; Jurikova, Lenka; Podborska, Martina; Mazanec, Radim; Dusek, Ladislav; Jarkovsky, Jiri; et al.
Abstract : Abstract: Some muscular dystrophies may have a negative impact on fertility. A decreased ovarian reserve is 1 of the factors assumed to be involved in fertility impairment. AMH (anti-Müllerian hormone) is currently considered the best measure of ovarian reserve. A total of 21 females with myotonic dystrophy type 1 (MD1), 25 females with myotonic dystrophy type 2 (MD2), 12 females with facioscapulohumeral muscular dystrophy (FSHD), 12 female carriers of Duchenne muscular dystrophy mutations (cDMD) and 86 age-matched healthy controls of reproductive age (range 18 – 44 years) were included in this case control study. An enzymatically amplified 2-site immunoassay was used to measure serum AMH level. The MD1 group shows a significant decrease of AMH values (median 0.7 ng/mL; range 0 – 4.9 ng/mL) compared with age-matched healthy controls ( P < .01). AMH levels were similar between patients and controls in terms of females with MD2 ( P = .98), FSHD ( P = .55) and cDMD ( P = .60). This study suggests decreased ovarian reserve in women with MD1, but not in MD2, FSHD and cDMD.